Propuesta para la reorganización pluridepartamental del Perú - Alcabés, Nissim (2007)
This paper discusses the transition from the present single-department regions to a structure of multiple-department regions. It discusses the convenience of creating a pilot region and provides some criteria to create multi-department regions and choose the location of the regional capitals. It also provides guidelines to elect representatives to the Chamber of Deputies and the creation of a Senate. Finally, it outlines eight regions to be created by grouping several departments, and an alternative proposal to create regions based on river drainage basins.